PENDAMPINGAN PENULISAN PENELITIAN R&D DAN JURNAL ILMIAH BAGI MAHASISWA - Rohani, Rohani (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2024)
This community service aims to find out the importance of writing R&D research and scientific journals for teachers. The background of this community service is student who are not used to writing R&D and scientific journals. The target of this community service activity is specifically Economics education Students. The methods used in this community service activity are presentations and practices as well as demonstrations. Based on the results of community service activities, mentoring in writing classroom action research and scientific journals went smoothly, the material provided could be understood by the participants so that they could practice directly